The influence of endometriosis peritoneal fluid on the development of mouse embryo in in vitro pre-implantation - Hasto Wardoyo, Ita Fauziah, O. Wahyu, Djaswadi Dasuki (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Endometriosis was associated with various immunologic changes detected both in the endometrial eutopic and blood edge sample. Some researchers reported that women with endometriosis have an increased amount of peritoneum fluid. Endometrial environment and peritoneal fluid diffusing to the ovarial tube may affect sperm-ovum interaction, initial phase of embryonic development and reduce endometrial receptability. The correlation between endometriosis and early in vitro embryonic development has been reported in some studies showing controversial results; therefore it is necessary to carry out researches to clarify the influence of endometriosis on the early embryonic development. Objective: to identify the influence of peritoneal fluid of infertile women with endometriosis and normal peritoneum fluid of fertile women on the development of mouse embryo in in-vitro pre-implantation. Methods: Prospective, randomized controlled trial subjects are 2 cells of the Swiss albino strain embryos super-ovulating procedure on mouse, 2 embryonic cells resulted from in-vivo fertilization were taken out and in-vitro culture was done with the exposure of 10% or 2.5% cell-free supernatant peritoneum fluid of infertile women with endometriosis and 10% or 2.5% cell-free supernatant peritoneum fluid of normal fertile women as the control. The blastocyst growth was observed in the 72 hour culture and hatching blastocyst culture in 96 hours. Results: An amount of 231 embryos of 2 cells was obtained. After 72 hours, there were 103 blastocyst cultures in both groups. Blastocyst development rate (BDR) culture with to endometriosis peritoneum fluid exposure was lower compared with the normal peritoneum fluid exposure (32.2% vs 56.9%, RR 0.5, 95% CI: 0.42-0.77). Hatching rate (HRI of blastocyst culture with endometriosis peritoneum fluid was lower than that of normal peritoneum fluid (35.1 % vs 92.4%, RR 0.38, 95%CI: 0.24-0.59). The exposure to 10% endometriosis peritoneum fluid lowered BDR significantly compared with the normal peritoneum fluid, 7.7% vs 43.9% (RR 0.18,95% CI: 0.07-0.42); while the exposure to 2.5 % BDR was significantly different, (64% vs 74%, RR 0.87,95% CI: 0.66-1.13). Exposure to 10% compared to 2.5% normal endometriosis peritoneum fluid showed significantly decreased BDR (p 0.05). There was a significant interaction between type of peritoneum fluid (endometriosis vs normal) and the concentration of peritoneum fluid (10% vs 2.5%1 in decreasing BDR (RR 0.17,95% CI: 0.04-0.65). Conclusion: Exposure to endometriosis peritoneum fluid lowered the blastocyst development rate and hatching rate as compared with that to normal peritoneum fluid on the development of the in- vitro mouse embryo model. Key words: embryonic development - peritoneum fluid - endometriosis